Sistem Penunjang Keputusan Seleksi Penerimaan Satpam Menggunakan Metode Topsis - Hilmi Surowardi; Fajar Septian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
This research aims to develop a Decision Support System (DSS) for the selection of security guards at PT. Reska Multi Usaha. The company faces challenges in determining criteria and objectively choosing the best security guards. An effective and efficient selection process is crucial to ensure that only high-quality candidates are chosen. In this study, software is developed using the Technique for Order Preferences by Similarity to Ideal Solution (TOPSIS) method as an approach to decision-making. The TOPSIS method enables the evaluation of potential security guards based on criteria such as physical abilities, security knowledge, work experience, and psychological test results. The implementation of this system is expected to improve the effectiveness and efficiency of the security guard selection process at PT. Reska Multi Usaha. This system assists management in evaluating potential security guards based on relevant criteria, facilitating objective and accurate decision-making. With this Decision Support System, it is hoped that only the best security guard candidates will join the company, enhancing security, the reliability of security services, and providing satisfaction to clients and customers.